Garap Kendhangan in Gendhing Lampah Tiga - Ananto Sabdo Aji (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2023)
This research plan intends to study, analyze, and explain comprehensively but in a more practical format regarding the interpretation and working of kendhang on the structure lampah tiga. Gendhing with the lampah tiga structure is one of the special gendhing structures because it has a bar where not many gendhing repertoires have this bar, so, of course, there are many problems for the composer, especially the ricikan kendang to present this gendhing structure, knowledge is needed to determine the interpretation and garap variant so that it can identify and present gendhing with structure. The method used is a descriptive analysis based on empirical knowledge. Empirical knowledge will help in analyzing the variety and interpretation of the lampah tiga structure, while the garap approach is used as a tool to dissect the musical situation in the intended gendhing structure. The qualitative descriptive data analysis method is carried out by observing the validity of the data through data triangulation. Accurate data collection through library research, interviews, and observations is expected to be able to explore the work on kendhangan gendhing lampah tiga. It is hoped that this research will be able to support teaching and learning activities in the form of textbooks, and it is hoped that it can add references to karawitan knowledge books.